Analisis Framing Pemberitaan Kasus Penganiayaan Mario Dandy Satriyo Terhadap David Ozora Pada Majalah Tempo (Periode Maret – Juli 2023) - Damayanti, Amalia; Saputra, Faisal Tomi; Alamsyah, Alamsyah (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this research is to analyze the news that is currently circulating in the news media and online about the children of tax officials who are abused by children from Banser in the period of March-July 2023. The researcher uses framing analysis in his research to frame the news, there are four stages of framing dimensions Robert N. Entman includes: Define Problem, Diagnose Cause, Make moral judgment and Treatment recommendation. This research uses Robert N. Entman's framing analysis method with a qualitative approach. Until finally there is a news phenomenon that is being widely reported which must have become a new attraction for the public, which is about the son of the former tax director named Mario Dandy is now in the media spotlight because it started from his lover who complained to Mario that he was allegedly threatened by his former lover, David Ozora. David Ozora is the son of Jonathan Lathumahina who is a member of the Cyber ​​Team of Central Management (PP) of GP Ansor, it is suspected that he does not want to break up with his lover Mario because of that, he threatened to spread evidence of indecent photos when he was with David, Mario who heard about it from the lover did not accept then set up a strategy to persecute David.